Analysis Of The Internal Control System For Raw Material Inventory At UD Saudara Jaya - Shalina Yulinar Nungkifani; Sampir Andrean Sukoco (CV. AFDIFAL MAJU BERKAH, 2026)
Raw material inventory is a crucial component that determines the smoothness of the production process, thus requiring an effective internal control system. This study aims to analyze the internal control system for raw material inventory at UD Saudara Jaya based on the Committee of Sponsoring Organizations of the Treadway Commission (COSO) framework. The study used a qualitative approach with a case study type. The research informants consisted of the management, the head of the raw material department, the head of the production department, and the administration department selected using a purposive sampling technique. Data were collected through observation, structured interviews, and documentation, then analyzed using the Miles and Huberman model which includes data condensation, data presentation, and drawing conclusions with validity tests through source and technique triangulation. The results of the study indicate that the five components of internal control have been implemented, but there are still weaknesses in inventory recording, documentation of evaluation results, and the use of technology that is still simple. The conclusion of the study shows that the internal control system for raw material inventory at UD Saudara Jaya has been running quite well in supporting smooth operations, but still requires improvement through digitalization of recording, strengthening control documentation, and increasing the use of information technology.